Analisis Pengaruh Program Keluarga Harapan (PKH) Di Kelurahan Gebang Putih, Kecamatan Sukolilo, Kota Surabaya - Adzra Ajeng Lestari; Dida Rahmadanik (Jurnal Media Administrasi, 2023)
The purpose of this study is to investigate the impact of the Family Hope Program (also known as PKH). In and of itself, the PKH program is a social assistance program that the Indonesian government launched in order to combat the country's high poverty rates. In this study, qualitative research methodologies and a descriptive approach are utilized, and interviews with various resource persons serve as the primary method for data gathering. The findings of this study showed that there were variations in the number of people who received PKH benefits over the course of the program's first five years of operation. In addition, there were variations in the lifestyles of people who received PKH benefits in the Gebang Putih Subdistrict. Despite the fact that the results were generally positive, this demonstrates that the implementation of PKH in the Gebang Putih Subdistrict was successful in reducing the level of poverty in the area. It is hoped that the Subdistrict assistants and the PKH assistants who are now on duty would continue to analyze the results of the program's implementation. In order for the percentage of people living in poverty to continue to fall, and for the inhabitants of Gebang Putih to be able to enjoy a higher standard of living.